Pengaruh Content Marketing, Celebrity Endorser, dan Electronic Word of Mouth Pada Media Sosial TikTok Terhadap Minat Beli Fashion (Studi Pada Generasi Z di Indonesia) - Nadia Aryani (Journal of Fundamental Management (JFM), 2022)
This study aims to analyze the effect of content marketing, celebrity endorser, and electronic word of mouth on TikTok social media on fashion purchasing intention. The population in this study is Generation Z in Indonesia who are TikTok social media users. The sample used was 200 respondents, which was obtained using purposive sampling method. The research method used is quantitative method, with data collection using survey methods. Analysis of the data used in this study is the Structural Equation Model (SEM), using the SmartPLS software version 3.0. This study proves that content marketing has a positive and significant effect on purchasing intention. Celebrity endorsers have a positive and significant effect on purchasing intention. Electronic Word of Mouth has a positive and significant effect on purchasing intention.